Changes in basement membrane components in an experimental model of skeletal muscle degeneration and regeneration induced by snake venom and myotoxic phospholipase A2 - Escalante Muñoz, Teresa (2021)
Skeletal muscle regeneration is impaired after myonecrosis induced by viperid snake venoms, but the mecha- nisms behind such poor regenerative outcome are not fully understood. This study compared the changes in basement membrane (BM) components in mouse skeletal muscle in two different scenarios of muscle injury: (a) injection of Bothrops asper venom, as a model of poor regeneration, and (b) injection of a myotoxic fraction (Mtx) isolated from this venom, as a model of successful regeneration. The degradation and reposition of laminin, type IV collagen and fibronectin were assessed over time by a combination of immunohistochemistry, Western blot, and real time polymerase chain reaction. Both treatments induced degradation of laminin and type IV collagen in areas of muscle necrosis since day one, however, there were differences in the pattern of degradation and reposition of these proteins along time. Overall, Mtx induced a higher synthesis of fibronectin and higher degradation of laminin at intermediate time points, together with higher levels of transcripts for the chains of the three proteins. Instead, venom induced a higher degradation of laminin and type IV collagen at early time in- tervals, followed by a reduced recovery of type IV collagen by 15 days. These differences in extracellular matrix degradation and remodeling between the two models could be associated to the poor muscle regeneration after myonecrosis induced by B. asper venom.